Vključevanje mladih brezposelnih oseb v aktivne politike zaposlovanja - Južnik, Laura (Naše gospodarstvo, 2008)
Active labour market policies are essentially public interventions in the labour market that target particular groups in the labour market. Measures for young people, for example, include only special programmes that are aimed at making the transition from school to work easier and quicker. Active labour market policies basically aim to increase the likelihood of employment or improve income prospects for the unemployed persons or groups who find it difficult to enter the labour market. According to this, the transition from passive to active measures becomes evident. With the use of binary choice models in the article we try to find the determinants of young unemployed persons' inclusion into employment programmes.
Keywords: Slovenia; Slovenija; mladi; trg delovne sile; zaposlovanje; zaposlitev; brezposelnost; unemployment